Artistic Horizons of Zhagafar Tokumayev's Creativity - Alena М. Sarbasheva (Кавказология, 2022)
The article examines the literary heritage of the famous Balkarian writer, playwright Zhagafar Tokumayev. The main purpose of the work is to fully present the panorama of the creative work of the master of the artistic word, to determine its role in the evolution of national written literature. The article is preceded by a short autobiographical reference focusing on the influence of the writer's life experience on the formation and development of his artistic consciousness. Tokumayev's creativity is considered from the point of view of genre, thematic diversity, the ethnocultural specificity of his works is determined. Analysis of the author's aesthetic experience in small and medium epic forms (stories "Agronomist", "Mistake", "Courage", "Investigator's Story"; the stories "The fate of the orphan", "Descendants of the sleds", "The Pass") it shows a wide thematic range (istroic, moral, social, household, detective) of works, reveals characteristic artistic features (the connection of times, the evolution of consciousness of the main actors at the sharp fractures of history and in extraordinary life circumstances). The article focuses on the trilogy of J. Tokumaeva's "Dagger of Revenge", recognized as the first experience of artistic cyclization in Balkar novelistics. The constructive role of Zh is also noted. Tokumaeva in the development of drama and stage art (comedies "Imaginary authority", "Shadows", "Jamilya", "Chonai marries", included in the "golden fund" of the repertoire of the Balkarian State Drama Theater named after K. Kuliyev). The versatility of the writer's talent is evidenced by children's prose ("The Stories of Aldarbek from Kurnayat"), humorous miniatures ("Mocker Chonai"). As a result of the study, the author's desire throughout his creative life to expand genre-thematic horizons in understanding artistic reality, which subsequently contributed to the enrichment of the spiritual culture of the Balkarian ethnic group.The article uses historical, comparative methods, the method of literary analysis.